Penerapan Metode Kriptografi Menggunakan Algoritma RSA untuk Keamanan Data Keluhan Pelanggan (Studi Kasus : PT. PLN UP3 Bali Timur Wilayah Klungkung) - Cayadewi, Ni Luh Putu Ayu Siwastuti; Raharja, Made Agung; Suhartana, I Ketut Gede; Cahyadi Putra, I Gusti Ngurah Anom (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2025)
Misuse of customer data document files can result in financial losses and damage the company's reputation. Therefore, companies must take steps to secure customer data, one of which is through cryptographic methods. This study uses the Rivest-Shamir-Adleman (RSA) algorithm which is known for its security to secure customer complaint data at one of the companies, namely PLN, especially in the Klungkung area. RSA was chosen because it has a long key and a high level of security, so it can protect data from potential theft. This study aims to design a web-based system that applies the RSA encryption method to protect customer complaint data document files. The results of this study are shown through black-box testing results that the entire encryption and decryption process works according to the designed scenario, where the document file in the form of .docx containing customer complaint data (report number, name, address, and complaint) is successfully encrypted into unreadable ciphertext, and can be returned to its original data form accurately through decryption, with an average bit change reaching 50.28%. With this step, it is hoped that customer privacy can be maintained, customer trust in the company can be increased, and the risk of data misuse can be minimized.